Triplen Harmonics Mitigation 3 Phase Four-Wire Electrical Distribution System Using Wye- Zig-Zag Transformers - Omar , Rosli; Ahmad, Azhar; Sulaiman , Marizan (jeteas.scholarlinkresearch.org, 2010)
This paper studies an application of wye- zigzag transformes for reducing harmonics in the neutral conductors of a three phase 415/240V distribution system. Triplen harmonic currents add up in the neutral conductor of the distribution system feeding the non linear loads such as personal computers and electronic office machines with switch mode power supplies. The zigzag transformer is installed between the distribution panel and the high harmonics producing loads. This research makes use of a star-zigzag grounded transformer.